2012
DOI: 10.1212/wnl.0b013e3182768954
|View full text |Cite
|
Sign up to set email alerts
|

A novel hereditary extensive vascular leukoencephalopathy mapping to chromosome 20q13

Abstract: These data establish that this family is affected by a novel autosomal dominant vascular leukoencephalopathy mapping to chromosome 20q13. This disease is characterized by a progressive and age-related hemispheric and brainstem leukoencephalopathy contrasting with the paucity and late onset of clinical symptoms in most of the cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…Other familial forms of vascular dementia include an autosomal dominant type of Swedish dementia not linked to CADASIL; and PADMAL, an autosomal dominant ‘subcortical angiopathic encephalopathy’ primarily affecting the pons, for which the causal gene is not known . A novel hereditary vascular leukoencephalopathy mapping to chromosome 20q13 (possibly related to CARASAL, see above) has been reported . Neuropathologic details of one case have been provided: this examination showed a combination of severe AD changes including CAA, and microvascular changes that (though not illustrated) appear to represent severe AS or lipohyalinosis.…”
Section: Hereditary (Cerebral) Microangiopathiesmentioning
confidence: 99%
“…Other familial forms of vascular dementia include an autosomal dominant type of Swedish dementia not linked to CADASIL; and PADMAL, an autosomal dominant ‘subcortical angiopathic encephalopathy’ primarily affecting the pons, for which the causal gene is not known . A novel hereditary vascular leukoencephalopathy mapping to chromosome 20q13 (possibly related to CARASAL, see above) has been reported . Neuropathologic details of one case have been provided: this examination showed a combination of severe AD changes including CAA, and microvascular changes that (though not illustrated) appear to represent severe AS or lipohyalinosis.…”
Section: Hereditary (Cerebral) Microangiopathiesmentioning
confidence: 99%
“…These changes caused the leukoencephalopathy to become virtually diffuse. Hervé et al reported a French family with autosomal-dominant vascular leukoencephalopathy with an MRI pattern similar to that in CARASAL [101,102]. Neuropathological findings included a diffuse white matter-and myelin pallor, asymmetric fibrous thickening in small arterioles or astroglyosis.…”
Section: Cathepsin A–related Arteriopathy With Strokes and Leukoenmentioning
confidence: 97%
“…First, the recent identification of distinct monogenic forms of SVDs has revealed that the distribution of WMHs may differ substantially among different hereditary SVDs. For instance, early extensive WMHs in the anterior temporal lobe are highly characteristic of CADASIL, whereas WMHs are mild or absent in this region in both cathepsin A-related arteriopathy with strokes and leukoencephalopathy (CARASAL) [7,61] and pontine autosomal-dominant microangiopathy with leukoencephalopathy (PADMAL) [6,62]. In contrast with other ischaemic hereditary SVDs, the severity of WMHs in CARASAL has been reported to be disproportionately extensive compared with lacunar infarcts, which are very rare [7,61].…”
Section: Heterogeneity Of Wmhsmentioning
confidence: 99%
“…For instance, early extensive WMHs in the anterior temporal lobe are highly characteristic of CADASIL, whereas WMHs are mild or absent in this region in both cathepsin A-related arteriopathy with strokes and leukoencephalopathy (CARASAL) [7,61] and pontine autosomal-dominant microangiopathy with leukoencephalopathy (PADMAL) [6,62]. In contrast with other ischaemic hereditary SVDs, the severity of WMHs in CARASAL has been reported to be disproportionately extensive compared with lacunar infarcts, which are very rare [7,61]. Second, longitudinal analyses of WMHs in elderly community-dwelling volunteers have shown that early, confluent WMHs, but not punctate WMHs, are actually progressive during follow-up [14].…”
Section: Heterogeneity Of Wmhsmentioning
confidence: 99%